Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1126/sciadv.add9554
|View full text |Cite
|
Sign up to set email alerts
|

The lactate dehydrogenase (LDH) isoenzyme spectrum enables optimally controlling T cell glycolysis and differentiation

Abstract: Isoenzyme divergence is a prevalent mechanism governing tissue-specific and developmental stage-specific metabolism in mammals. The lactate dehydrogenase (LDH) isoenzyme spectrum reflects the tissue-specific metabolic status. We found that three tetrameric isoenzymes composed of LDHA and LDHB (LDH-3/4/5) comprise the LDH spectrum in T cells. Genetically deleting LDHA or LDHB altered the isoenzyme spectrum by removing all heterotetramers and leaving T cells with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Compared with the drastically decreased RocF activity, ArgG seemed to retain most of its activity, which seems to imply that the isofunctional enzymes of ArgG may be present in Bt. Organisms often have multiple replacement genes or proteins for important enzymes or proteins 27 In fact, according to the GO annotations of genome sequencing in our previous work, 25,26 two presumptive isofunctional genes (BSP001038 and BSP001049) were detected in Bt LLP29. In addition, because ArgG is a ratelimiting enzyme for arginine synthesis, its expression level is usually very low.…”
Section: Discussionmentioning
confidence: 96%
“…Compared with the drastically decreased RocF activity, ArgG seemed to retain most of its activity, which seems to imply that the isofunctional enzymes of ArgG may be present in Bt. Organisms often have multiple replacement genes or proteins for important enzymes or proteins 27 In fact, according to the GO annotations of genome sequencing in our previous work, 25,26 two presumptive isofunctional genes (BSP001038 and BSP001049) were detected in Bt LLP29. In addition, because ArgG is a ratelimiting enzyme for arginine synthesis, its expression level is usually very low.…”
Section: Discussionmentioning
confidence: 96%
“…Down-regulation of LDHB expression disrupts lactate-to-pyruvate conversion, leading to impaired mitochondrial ATP production and inhibition of oxidative phosphorylation. Overexpression of LDHB in mouse muscle enhances mitochondrial gene expression and respiratory capacity [59,60]. MLC1, also known as astrocyte membrane protein 1, played a crucial role in cerebral neurovascular development and physiology [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Lactate dehydrogenase (LDH) isozymes are tetramer of the translation products of the LDHA and LDHB genes. Chen et al [26] found that deletion of LDHA inhibited glycolysis, cell proliferation and differentiation, whereas deletion of LDHB promoted glycolysis but inhibited T-cell differentiation. In CD8+ effector T cells, the glycolytic enzyme lactate dehydrogenase A (LDHA) is induced by phosphoinositide 3-kinase (PI3K) signaling, and ablation of LDHA inhibits protein kinase B (AKT) and forkhead box 1 (Foxo1) activity, leading to decreased T cell effector function.…”
Section: Glucosementioning
confidence: 99%